The Development of Science Process Skills and Academic Achievement in Chemistry of Matthayom Sueksa Five Students at Ramkhamhaeng University Demonstration School Using the Peer-Assisted Technique. - Sa-ngiamjit, Maneerat (European Journal of Sustainable Development, 2016)
In this research investigation, the researcher compares (1) the academic achievement in organic chemistry of selected Matthayom Sueksa Five students instructed by means of the peer-assisted technique. The researcher also describes and analyzes (2) the fostering of science process skills of these students utilizing the peer-assisted technique. Using the simple random sampling method, the researcher selected a sample population constituting a single Matthayom Sueksa Five (Science-Math) classroom at the Ramkhamhaeng University Demonstration School (DSRU) of such students enrolled in the second semester of the academic year 2015. The research instruments consisted of an academic achievement test on organic chemistry couched at the validity level of 0.82 and a test used for measuring science process skills couched at the validity level of 0.75. Using techniques of descriptive statistics, the researcher analyzed the data collected in terms of mean and standard deviation. A t-test technique was also employed by the researcher. Findings are as follows: (1) The students taught using the peer-assisted technique exhibited a higher level of academic achievement in organic chemistry after the study was completed than prior to the commencement of the study at the statistically significant level of .05. (2) After the completion of the study, these students showed improvement in science process skills at the statistically significant level of .05. Keywords: Science Process Skills, students, peer-assisted technique, academic achievement